THE INFLUENCE OF THE MNEMONIC LEARNING MODEL ON THE LEARNING OUTCOMES OF ARTS, CULTURE, AND CRAFTS (SBDP) IN CLASS IV SDN PANNARA, MAKASSAR CITY - Cayati, Cayati; Yuspida, Yuspida; Sabillah, Bellona Mardhatillah (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2024)
ABSTRACTThis study aims to determine whether the mnemonic learning model influences the learning outcomes of arts and crafts (SBdP) for fourth grade students at SDN Pannara, Makassar City. The research method employed was quantitative experimental research with a one-group pretest-posttest design, and the subjects were fourth-grade elementary school students with collage-related two-dimensional expression work material. This study employs research test instruments, observation sheets, and documentation. In this study, descriptive statistical analysis and inferential statistical analysis were used to analyze the data. Fourth-grade students of SDN Pannara Makassar City whose learning outcomes were enhanced by the application of the mnemonic learning model, as demonstrated by the study's findings. This is demonstrated by testing the hypothesis with the t-test and the test results, namely a significance of 0.000 0,000 < α 0,05 which means that H1 is accepted and H0 is rejected. Where H1 asserts that SBdP learning outcomes for fourth-grade students at SDN Pannara have improved because of the use of the mnemonic learning model. While H0 claimed there was no improvement in SBdP learning outcomes for fourth-grade students at SDN Pannara because of the use of the mnemonic learning model, this study found otherwise. The average student score, which ranges from 30.67 on the pre-test to 90.95 on the post-test, further demonstrates this point. The use of the mnemonic learning model improved the learning outcomes of fourth grade students of SDN Pannara in Makassar City. Therefore, it is recommended that teachers, especially of SBdP subjects, consider using the mnemonic learning model in SBdP learning to make the teaching and learning process more effective, enjoyable, and engaging.